Metabolomics and transcriptomics indicate the changes in medicinal components of Amygdalus mongolica kernels during different developmental stages - Lei, Zhenyu; Chang, Hong; Song, Li; Zhou, Hongbing; Bai, Wanfu; Bai, Yingchun; Jiang, Shuyuan; Shi, Songli; Wang, Jia (Frontiers in Plant Science, 2025)
Amygdalus mongolica is a traditional Chinese and Mongolian medicine and is quite effective in relieving cough and eliminating phlegm. In this study, ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS) was used to perform metabolomics analysis, combined with transcriptomic sequencing, to study the samples of A. mongolica at early, middle and late growth stages. A comprehensive analysis was conducted to systematically investigate the dynamic changes and developmental trajectories of kernel progression across distinct growth stages, utilizing differential expression analysis and pathway enrichment approaches. A total of 104 significant differential metabolites were identified across different growth stages: the early growth stage (E), the middle growth stage (M), and the late growth stage (L). Specifically, 68 and 36 differential metabolites were detected in the comparisons of E vs. M and M vs. L, respectively. Among them, 29 and 21 metabolites exhibiting up-regulation. In comparison, 39 and 15 metabolites demonstrated down-regulation. Transcriptomic analysis identified 133 differentially expressed genes associated with 62 pathways in the E vs. M. Simultaneously, 14 differentially expressed genes linked to 13 pathways in the M vs. L. The accumulation of various metabolites varied across the growth stages, with a marked increase in amino acids during the middle and late developmental phases, alongside fluctuations in the levels of flavonoid compounds. In conclusion, the study reveals significant variations in the content and types of amino acid compounds and the expression levels of key genes within relevant pathways of A. mongolica kernels throughout different growth stages. Especially, the increase in flavonoid compound expression with advancing growth stages highlights their substantial medicinal potential. These findings provide a foundation for future developing and utilizing valuable medicinal ingredients in A. mongolica kernels.